Hukuman Mati dalam Perspektif Pidana dan HAM - Felix Eka Firtin Smit Kandun Mas; Sagung Putri M. E. Purwati (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
Writing journal about "death penalty from a criminal and human rights perspectiveis " is to find and describe how the application of death penalty to date, in which there are several countries that apply it to as a payment and even the punishment must be accepted by someone who has violated the provisions of regulations in a country. There are Countries Applied death penalty include China, Saudi Arabia, Iran, the Indonesia and United States. In all countries there are various types of capital punishment, but the most commonly used are shooting and death row Implementation of death penalty in the Criminal Code is only regulated by Article 11 with the compiler R. Soesilo As the formula: the execution of death penalty is imposed by a judicial institution within the military court or general court, with a procedure of being shot to death in accordance with the provisions of Law No. 2 (PNPS) of 1964 However, death penalty contradicts of notion by human rights as described in article 3 of the DUHAM which states that the most extreme form of violation of the right to life is killing or injuring a person or group of people physically or mentally.